The Effects of Changing Attention and Context in an Awake Offline Processing Period on Visual Long-Term Memory - Ellmore, Timothy M.; Feng, Anna; Ng, Kenneth; Dewan, Luthfunnahar; Root, James C. (Frontiers in Psychology, 2016)
There is accumulating evidence that sleep as well as awake offline processing is important for the transformation of new experiences into long-term memory. Yet much remains to be understood about how various cognitive factors influence the efficiency of awake offline processing. In the present study we investigated how changes in attention and context in the immediate period after exposure to new visual information influences long-term memory consolidation. After presentation of multiple naturalistic scenes within a working memory paradigm, recognition was assessed 30 minutes and 24 hours later in three groups of subjects. One group of subjects engaged in a focused attention task (the Revised Attentional Network Task (R-ANT)) in the 30 minutes after exposure to the scenes. Another group of subjects remained in the testing room during the 30 minutes after scene exposure and engaged in no goal- or task-directed activities. A third group of subjects left the testing room and returned 30 minutes later. A signal detection analysis revealed no significant differences among the three groups in hits, false alarms, or sensitivity on the 30-minute recognition task. At the 24-hour recognition test, the group that performed the R-ANT made significantly fewer hits compared to the group that left the testing room and didn’t perform the attention ask. The group that performed the R-ANT and the group that remained in the testing room during the 30-minute post-exposure interval made significantly fewer false alarms on the 24-hour recognition test compared to the group that left the testing room. The group that stayed in the testing room and engaged in no goal- or task-directed activities exhibited significantly higher sensitivity (d’) compared to the group that left the testing room and the group that performed the R-ANT task. Staying in the same context after exposure to new information and resting quietly with minimal engagement of attention results in the best ability to distinguish old from novel visual stimuli after 24 hours. These findings suggest that changes in attentional demands and context during an immediate post-exposure offline processing interval modulate visual memory consolidation in a subtle but significant manner.